Projeto arquitetônico de um centro de dança para a cidade de São Luís - Alves, Paula Palmeira (2011)
It is a proposal for an architectural preliminary draft of a Dance Center, located on Avenue of the Holandeses in the neighborhood of the Renascença II, in São Luís (MA). Presents general definitions, history, origin, classification and main forms of dance in Brazil. It analyzes Dance Centers in the world, in Brazil and in São Luís, seeking to define parameters that the program needs to be compatible with local realities. It is proposed that a preliminary draft of Dance Centre, differentiated, and a mixed team, institutional and trade, including a program needs complete with activities and diverse forms, but related to the same issue.